Predictors of Malignancy in Thyroid Nodules Classified as Bethesda Category III - Liu, Xiaoli; Wang, Jingjing; Du, Wei; Dai, Liyuan; Fang, Qigen (Frontiers in Endocrinology, 2022)
Objective To determine predictors of malignancy in surgically treated Bethesda category III nodules. Methods Patients with surgically treated thyroid nodules classified as Bethesda category III were retrospectively enrolled. The association between clinical/sonographic features and postoperative pathology was evaluated using univariate and multivariate analyses. Results A total of 188 nodules from 184 patients were included. The overall malignancy rate was 54.3%. In univariate analysis, male sex, aspect ratio >1, microcalcification, unclear boundary, BRAFV600E mutation, and nuclear atypia were significantly associated with malignant disease in Bethesda category III nodules. Multivariate analysis confirmed that male sex, aspect ratio >1, microcalcification, and BRAFV600E mutation were independent predictors of malignant disease. Conclusions Malignant disease was common in Bethesda category III nodules, and surgical treatment was strongly indicated in the presence of male sex, aspect ratio>1, microcalcification, and BRAFV600E mutation.